Analisis Kesiapan Guru Sekolah Dasar Dalam Mengintegrasikan Artificial Intelligence Pada Proses Pembelajaran - Atika Islamiah; Ayana Lestariani; Nana Aprilia (PGSD UNU NTB, 2024)
This study aims to analyze elementary school teachers' readiness to integrate Artificial Intelligence into the learning process and identify influencing factors. A quantitative approach was used with a survey design for teachers as respondents. Data were collected through a structured questionnaire measuring AI literacy, self-efficacy, performance expectations, ease of use, institutional support, and readiness level. Data analysis was conducted descriptively and inferentially using multiple linear regression and Structural Equation Modeling. The results indicate that teacher readiness is in the moderate to high category. Teachers have positive perceptions of AI use, but are still limited in technical skills and practical experience. AI literacy and self-efficacy are the dominant factors, followed by performance expectations, ease of use, and institutional support. Institutional support also plays an indirect role by increasing competence and confidence. The use of AI is still basic and not optimal for adaptive learning. These findings indicate that teacher readiness is multidimensional and requires a comprehensive approach. Therefore, practice-based training, strengthening AI literacy, and ongoing institutional support need to be improved.